Kepemimpinan Guru PAK dalam Membentuk Kompetensi Diri Generasi Quantum Menuju Indonesia Emas 2045 - Febrianus Selvin Sudiman; Elvin Jernih Sari Zebua; Cristian Seldjatem (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
Christian Religious Education (PAK) teacher leadership plays a crucial role in shaping the self-competence of the Quantum generation that can contribute to the Golden Indonesia 2045. The Quantum Generation, which is growing up in a digital era and rapid technological advances, requires leaders who are not only able to provide knowledge, but also guide them to have the character, emotional intelligence, and social skills needed to face global challenges. PAK teachers serve as role models, instilling Christian values that include honesty, compassion, empathy and responsibility. In addition, they also serve as a guide in building students' emotional intelligence so that they can manage their feelings and interact positively in a fast-paced society.The method used in this research is a qualitative approach, which focuses on an in-depth understanding of the role of PAK teachers in shaping students' self-competence through interviews, observations, and literature studies. The main objective is to explore and analyze how the leadership of PAK teachers can shape the character, emotional intelligence, and social skills of the Quantum generation. Through this debriefing, it is hoped that Indonesia's young generation can have balanced competence between intellectual and spiritual intelligence, be ready to face future challenges, and contribute to the achievement of the Golden Indonesia 2045.